Agronomic efficiency of nitrogen fertilizers on green harvesting sugarcane ratoon - Vieira Megda, Michele Xavier; Trivelin, Paulo Cesar Ocheuze; Franco, Henrique Coutinho Junqueira; Otto, Rafael; Vitti, André César (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the agronomic efficiency of the nitrogen sources urea (U), ammonium nitrate (AN), ammonium sulfate (AS), and ammonium chloride (AC) on green harvesting sugarcane ratoon, as well as the residual effect of these sources on crop productivity in the subsequent crop year. A randomized block design was used with four replicates. Treatments consisted of applying 120 kg ha-1 of N fertilizer on a Typic Hapludox covered by straw residues resulting from the harvest without burning of the first ratoon. A control treatment was included with no N fertilizer. To evaluate the residual effect of the nitrogen fertilizers, 450 kg ha-1 of a 20‑5‑19 formulation was applied to soil after sugarcane ratoon harvest. The highest production of stalks and sugar, in the 2006/2007 season, was obtained with the source AS. In the 2007/2008 harvest season, no residual effect of N fertilization was observed and there was a productivity decrease in the AC treatment in comparison to the control. The AC source, at a dose of 120 kg ha-1 N in the fertilization of the second ratoon, is agronomically as efficient as the other N sources used, but shows less efficiency in the subsequent crop year.
Keywords: Saccharum; ammonium chloride; residual effect; nitrogen